Power chord - Staunton, Ted (Victoria, BC : Orca Book Publishers, 2011)
Fourteen-year-old Ace starts a band and learns a tough lesson about plagiarism.
"RL 2.5"--Cover p. [4].
Keywords: Bands (Music) -- Juvenile fiction; Rock music -- Juvenile fiction; Contests -- Juvenile fiction; Performing arts -- Juvenile fiction; Plagiarism -- Juvenile fiction